WATER DEFICIT EFFECT ON GROWTH OF YOUNG FAST GROWING TEAK (Tectona Grandis L.F.) (PENGARUH DEFISIT AIR TERHADAP PERTUMBUHAN JATI EMAS MUDA) - E. Eliyani; I Handoko; Yonny Koesmaryono (Agromet, 2005)
Teak (Tectona grandis L.f.) has been grown in Indonesia since the beginning of 14th century. Teak forests in Indonesia are found mainly on the island of Java, which cover an area of about 1 million ha (Indonesia Forest State Enterprise, 1992). Outside Java, the natural area of teak is Muna Island, Southeast Sulawesi (Simon, 1997). In some recent years, teak has been planted in some other islands of Indonesia from Sumatra to Papua mainly by private sectors and farmers. Some of these plantations are in areas that would have been considered marginal for teak growing two decades ago.This phenomenon was encouraged by relatively new perception of teak planting as a commercially profitable venture, as well as by policy and legal changes. The rotation cycle of new high-intensity teak plantations is generally between 20 and 25 years which is three to four times shorter than for older low-intensity plantations (Nair & Souvannavong, 2000). Nowadays, the government does not control its harvesting and utilization for teak grown on private land.However, information on growth response of this kind of teak to climate is very limited. The fast growth of this kind of teak needs a specific environment that could be different for the slow growing one. Its resistance to water deficit may not be as high as the slow growing one as its needs much water to cover its fast growth particularly in the early period of growth. This experiment was intended to analyze the effects of water deficit to the growth of young fast growing teak.